A generation of Italian economists - Enrico Nano; Ugo Panizza; Martina Viarengo (Graduate Institute of International and Development Studies, 2021)
We examine the role of financial aid in shaping the formation of human capital in economics. Specifically, we study the impact of a large merit-based scholarship for graduate studies in affecting individuals' occupational choices, career trajectories, and labor market outcomes of a generation of Italian economists with special focus on gender gaps and the role of social mobility. We construct a unique dataset that combines archival sources and includes microdata for the universe of applicants to the scholarship program and follow these individuals over their professional life. Our unique sample that focuses on the high end of the talent and ability distribution also allows us to analyze the characteristics of top graduates, a group which tends to be under-sampled in most surveys. We discuss five main results. First, women are less likely to be shortlisted for a scholarship as they tend to receive lower scores in the most subjective criteria used in the initial screening of candidates. Second, scholarship winners are much more likely to choose a research career and this effect is larger for women. Third, women who work in Italian universities tend to have less citations than men who work in Italy. However, the citation gender gap is smaller for candidates who received a scholarship. Fourth, women take longer to be promoted to the rank of full professor, even after controlling for academic productivity. Fifth, it is easier to become a high achiever for individuals from households with a lower socio-economic status if they reside in high social mobility provinces. However, high-achievers from lower socio-economic status households face an up-hill battle even in high social mobility provinces.
Keywords: I22; I24; J16; J24; 330; Human capital formation; Financial aid; Career trajectories; Gender gaps